ANALISA TEBAL PERKERASAN LENTUR DENGAN METODE SNI 1989 DAN METODE NCSA (NATIONAL CRUSHED ASSOCIATION DESIGN) PADA RUAS JALAN PENDIDIKAN KABUPATEN BALANGAN. - Rosehan Anwar (Universitas Lambung Mangkurat, 2012)
Along with the development of a more advanced civilization, then the existence of an adequate road transportation is preferred. To support this Balangan county government make policy / program that is handling the construction and improvement of roads, routine and periodic maintenance. The policy is to achieve a smooth road services, safe and comfortable. So that development activities in the area there is no constraint. Way to memenuhu smoothness, safety and comfort requirements would have a thickness of the layers according to the circumstances existing subgrade. On that basis then, in the final writing, the author raised the title of Flexible Pavement Thickness Analysis Methods With ISO 1989 And Methods NCSA (National Crushed Association Design) At Toll Road District Education Balangan.The purpose of the writer was to determine thick flexible pavement with ISO 1989 method and the method of NCSA (National Crushed Association Design). Based on secondary data using the ISO 1989 obtained the results of calculations for the surface layer lataston HRS-WC with 3 cm thick HRS-BASE 4 cm thick, the base layer of crushed stone class A with 20 cm thick, and a layer of crushed stone foundation below grade B with a thickness of 10 cm. With the NCSA method to get a thick layer with a thick surface layer lataston 5 cm, the base layer of crushed stone class A 10 cm thick layer of crushed stone foundation under class B with a thickness of 25 cm.Of the two methods above can be known methods NCSA at the surface layer and the base layer is thinner, but to the method NCSA foundation layer 15 cm thicker than the method of ISO 1989.